2003
DOI: 10.1016/s0002-9440(10)63588-2
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effects of iNOS on Acute Lung Inflammatory Responses in Mice

Abstract: The role of endogenous NO in the regulation of acute lung injury is not well defined. We investigated the effects of inducible nitric oxide synthase (iNOS) and endothelial NOS (eNOS) on the acute inflammatoryThere is abundant evidence that lung inflammatory injury, occurring after a variety of insults, is due to activation of lung phagocytic cells, which produce numerous chemokines (reviewed).1 CXC chemokines are thought to attract neutrophils into the lung, while CC chemokines attract lymphocytes and monocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
123
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(135 citation statements)
references
References 50 publications
11
123
1
Order By: Relevance
“…It is well known that LPS injures lung endothelial and epithelial cells and enhances lung permeability [27]. Recently it has been shown that acute lung injury can be attenuated by reduction of lung hyperpermeability [28]. In this study we observed that endotoxin inhalation led to elevated albumin levels in bronchoalveolar lavage, which is marker of increased lung epithelial permeability.…”
supporting
confidence: 54%
“…It is well known that LPS injures lung endothelial and epithelial cells and enhances lung permeability [27]. Recently it has been shown that acute lung injury can be attenuated by reduction of lung hyperpermeability [28]. In this study we observed that endotoxin inhalation led to elevated albumin levels in bronchoalveolar lavage, which is marker of increased lung epithelial permeability.…”
supporting
confidence: 54%
“…The present study revealed a biphasic pattern of iNOS expression: early overexpression during the fractionated protocol, followed by delayed suppression, seen at 6 mo. In particularly, iNOS regulates chemokine expression involved in leukocyte (especially neutrophil) trafficking: the absence of iNOS enhances lung inflammatory responses, associated with increased production of MCP-1 by endothelial cells and macrophages [26] . Reports about iNOS regulation of the production of this CC chemokine are contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…iNOS gene-deficient mice injected with lipopolysaccharide (LPS) have been reported to show an increased resistance to lethality but a decreased resistance to bacterial inoculation (12,29). It has been reported that iNOS-derived NO suppresses tissue damage in acute lung injury; it acts to block the generation of chemokines (23) or inhibits sepsis-induced pulmonary apoptosis (22). Thus, iNOS-derived NO has both a beneficial effect (defence against infectious Numerous studies have been done concerning the relationship between the benefits and costs of inhibiting NO production in septic models (5,10,26,28,30).…”
mentioning
confidence: 99%